Field evaluation of the symbiotic fixation abilities among Rhizobium phaseoli strains - Salto, S.M.T. (Pesquisa Agropecuaria Brasileira, 2014)
Continuing the Programme of Field Inoculation with Rhizobium phaseoli, started in 1978, two experiments were carried out in TRE soil, the selection was based on the increase of weight and/or total N in the seeds and in the infection percentage by ten selected strains. In both soils, a significant increase in the nodulation of inoculated plants was observed. Probably due to the presence of a high N content in the first soil (TRE-1), no significant differences were observed in the plant growth due to inoculation. But increases up to 48% in the yield and up to 23% in the total-N of the grains were obtained in plots inoculated with the strains CIAT-903 and CIAT-640, estimating contributions of both strains, respectively 24.2 and 27.8 kg/ha of N from N2 fixation. In the second soil (TRE-2), although the evident increases in the vegetative growth of plants inoculated with CIAT-632, CIAT-676 and CIAT-903, a significant increase of 47% in the grain yield was obtained only when the bean was inoculated with CIAT-903, but contributed only with 2.86 kg/ha of fixed N.